2012
DOI: 10.1017/s003382220004738x
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Chronology for Prehistoric Complexes of the Russian Far East: 15 Years Later

Abstract: ABSTRACT. The recent progress in radiocarbon dating of the prehistoric cultural complexes in the Russian Far East is discussed against the background of ancient chronologies for greater East Asia. Since 1997, the wide use of accelerator mass spectrometry (AMS) radiocarbon dating along with the continuation of conventional dating has allowed us to establish the age of several key Paleolithic, Neolithic, and Paleometal sites. It has also contributed to advancing a deeper understanding of the timing for the begin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Kuzmin 1997. The site is 14 C dated to ~6700-5500 BP (charcoal) (Kuzmin 2012). The Chertovy Vorota site is located in a limestone cave ~30 km from the seashore; it is abundant in remains of terrestrial mammals, birds, and some anadromous fish (salmon) (e.g.…”
Section: Prehistoric and Medieval Dietary Patterns In Russian Far Eastmentioning
confidence: 99%
“…Kuzmin 1997. The site is 14 C dated to ~6700-5500 BP (charcoal) (Kuzmin 2012). The Chertovy Vorota site is located in a limestone cave ~30 km from the seashore; it is abundant in remains of terrestrial mammals, birds, and some anadromous fish (salmon) (e.g.…”
Section: Prehistoric and Medieval Dietary Patterns In Russian Far Eastmentioning
confidence: 99%
“…Age estimates for the Boisman culture obtained in our study can be compared to previously reported age estimates based on charcoal and human bones found at the Boisman 2 site. Kuzmin et al (1998) and Kuzmin (2012) dated the Boisman culture artifacts to between 6355 and 4470 BP. They also dated nine specimens of human bone to between 6080 and 5690 BP, which, after correction for the marine 14 C reservoir effect, translates to 5780–5390 BP (Kuzmin et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…They also dated nine specimens of human bone to between 6080 and 5690 BP, which, after correction for the marine 14 C reservoir effect, translates to 5780–5390 BP (Kuzmin et al 2002). Residues on the proto-Boisman type pottery have previously been dated to 7010 BP (Kuzmin 2012). In this study, we dated the proto-Boisman type pottery to between 7160 and 6730 BP and the Boisman culture specimens to between 6155 and 4870 BP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many theories have been proposed regarding the functions and uses of pottery in the early Neolithic in Northeast Asia on the basis of pottery shapes (capacity and type) and stone artifact composition, changes in the natural environment, the beginning of river fishing, and the use of nuts. Recent results show that pottery emerged in 3 regions of East Asia (south China, the Japanese Islands, and the Russian Far East), and it seems that the combination of environmental changes and the necessity of processing terrestrial plants and freshwater fish and mollusks resulted in the production of pottery-making in East Asia (Kuzmin 2010). The emergence of pottery was a groundbreaking event in prehistoric East Asia.…”
Section: Introductionmentioning
confidence: 99%